Spectral imaging and nucleic acid mimics fluorescence in situ hybridization (SI-NAM-FISH) for multiplex detection of clinical pathogens - Azevedo, Andreia S.; Fernandes, Ricardo M.; Faria, Ana R.; Silvestre, Oscar F.; Nieder, Jana B.; Lou, Chenguang; Wengel, Jesper; Almeida, Carina; Azevedo, Nuno F. (Frontiers in Microbiology, 2022)
The application of nucleic acid mimics (NAMs), such as locked nucleic acid (LNA) and 2′-O-methyl-RNA (2’OMe), has improved the performance of fluorescence in situ hybridization (FISH) methods for the detection/location of clinical pathogens, since they provide design versatility and thermodynamic control. However, an important limitation of FISH techniques is the low number of distinguishable targets. The use of filters in fluorescence image acquisition limits the number of fluorochromes that can be simultaneously differentiated. Recent advances in fluorescence spectral image acquisition have allowed the unambiguous identification of several microorganisms in a single sample. In this work we aimed to combine NAM-FISH and spectral image analysis to develop and validate a new FISH variant, the spectral imaging-NAM-FISH (SI-NAM-FISH), that allows a multiplexed, robust and rapid detection of clinical pathogens. In the first stage, to implement/validate the method, we have selected seven fluorochromes with distinct spectral properties and seven bacterial species (Pseudomonas aeruginosa, Citrobacter freundii, Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae, Escherichia coli and Acinetobacter calcoaceticus). As a strong variation in fluorescence intensities is found between species and between fluorochromes, seven versions of a EUB LNA/2’OMe probe, each conjugated to one of seven fluorochromes, were used to rank species/fluorochromes by FISH and then optimize species/fluorochromes pairing. Then, final validation tests were performed using mixed populations to evaluate the potential of the technique for separating/quantifying the different targets. Overall, validation tests with different proportions of bacteria labelled with the respective fluorochrome have shown the ability of the method to correctly distinguish the species.